Religious warfare in Europe, 1400-1536 - Housley, Norman (Oxford University Press, 2008)
Religious warfare has been a recurrent feature of European history. In this study, Norman Housley describes and analyses the principal expressions of holy war in the period, from the Hussite wars, to the first generation of the Reformation.